(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
In recent years, the forest-steppe zone of Ukraine has fallen into rather tough agro-climatic conditions; hence, new farming algorithms and methods should be developed. The economic use of sorghum is quite wide: it is a food, fodder, and technical crop, which is able to take advantage of minimal precipitation and tolerate high temperatures. Various fertilizer formulations, doses, and application timeframes are recommended for different pedo-climatic zones. Therefore, further research into fertilizer formulations, doses, and application methods is relevant. In previous years, a lot of scientists studied the application of various doses of mineral fertilizers and different methods of mineral fertilization under divers pedo-climatic conditions and described their effects in combination with different methods of soil cultivation: V.V. Ivanina, K.L. Pashynska (2017–2019), S.M. Kalenska, V.S. Naidenko (2015–2017), V.M. Maliarchuk, V.V. Sydorenko, A.S. Maliarchuk (2018–2020) and others. Records, observations and measurements of plants were carried out in accordance with the methods of B. O. Dospekhov, A. O. Nychyporovych, F. M. Kuperman et al. The study was conducted in the experimental field of the State Biotechnological University in 2021, 2023–2024. The two-factor experiment had split-plot design and was carried out in triplicate. The effects of different formulations and doses of fertilizers (Dura SOP and Renovation Fuerza) on the growth and development of durra sorghum hybrids ‘Aggil’ and ‘Brigga’ were studied. Different climatic conditions in the study years made it possible to identify the optimal formulations and doses of mineral fertilizers for the tested durra sorghum hybrids. It was found that the fertilization with Dura SOP and Renovation Fuerza at doses of 80 and 100 kg/ha significantly extended the growing periods in both hybrids compared to the absolute and zonal controls and extended the phenological phases such as emergence and stem growth. Observations of the plant growth and development over time showed that durra sorghum hybrids ‘Aggil’ and ‘Brigga’ responded positively to the mineral fertilization with Dura SOP and Renovation Fuerza. From emergence till ripening, plants of both hybrids were taller and heavier and formed larger leaves.